2000
DOI: 10.1111/j.1151-2916.2000.tb01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Mullite Whiskers Grown from Erbia‐Doped Aluminum Hydroxide–Silica Gel

Abstract: Mullite whiskers and anisotropic grains that were derived from erbia-doped aluminum hydroxide-silica gel were studied. Firing 3.0-mol%-erbia-doped isostatically pressed pellets at 1600°C for 1.0 -8.0 h resulted in a high surface concentration of mullite whiskers. Their c-axes were aligned preferentially along the pellet surface; the maximum length was 50 m, and the maximum aspect ratio was 23. The pellet surface was fully covered by mullite whiskers, and small anisotropic grains with a low aspect ratio were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…In previous research, anisotropic grains were observed in Aldeficient mullite prepared by solid-state method [20,21]. However, anisotropic grains were observed in Al-rich mullite by MSS.…”
Section: Characterization Of Whiskers: Effect Of Al/si On Compositionmentioning
confidence: 86%
See 1 more Smart Citation
“…In previous research, anisotropic grains were observed in Aldeficient mullite prepared by solid-state method [20,21]. However, anisotropic grains were observed in Al-rich mullite by MSS.…”
Section: Characterization Of Whiskers: Effect Of Al/si On Compositionmentioning
confidence: 86%
“…Besides the sort of starting materials, Al/Si ratio of starting materials is another factor that has a significant effect on the composition and morphology of mullite [19]. In mullite whiskers synthesized by solid-state reaction [20,21], Si-rich composition was suggested to facilitate the growth of anisotropic mullite that contained low Al 2 O 3 content (i.e. <60 mol% Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particle size of the amorphous silica, quartz and fused silica powders was 20-30 m. First, Al2(SO4)3·18H2O were calcined at 300 • C for 3 h to obtain Al2(SO4)3. According to the former research results that the Si-rich composition is beneficial for needlelike mullite grains formation [15,16], the constant composition [Al2(SO4)3:SiO2 = 2.5:1(wt%)] was employed in all samples. For the samples with various Na2SO4 contents, Al2(SO4)3 and Na2SO4 by weight percentage (wt%) as 2.5:14, 2.5:7, 2.5:3.5, and 2.5:1.75 were used and present by solid circles in Al2(SO4)3-Na2SO4 phase diagram [17] (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The raw topaz was processed either by wet ball milling for several hours with 10-mm-high alumina balls, then dried and crushed into powders or just grinding by a mortar and pestle, followed by mixing with 0.5 wt.% of AlF 3 1, the decomposition experiments were carried out at a programmed heating profile with maximum temperature 1300 jC for 4 h and some for 1 h under continuous flow of air, which was supplied by compressed air pump and measured by counting the bubble in a paraffin oil, or sometimes, water. NaOH water solution (5%) was used to absorb the off-gases from the system.…”
Section: Preparationmentioning
confidence: 99%